Reviews of Environmental Contamination and Toxicology 201 - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2009)
Foreword Preface Monitoring and Reducing Exposure of Infants to Pollutants in House Dust John W. Roberts, Lance A. Wallace, David E. Camann, Philip Dickey, Steven G. Gilbert, Robert G. Lewis, and Tim K. Takaro Pulmonary Toxicity and Environmental Contamination: Radicals, Electron Transfer and Protection by Antioxidants Peter Kovacic and Ratnasamy Somanathan Risk Assessment of Pseudomonas aeruginosa in Water Kristina D. Mena and Charles P. Gerba Non-thermal Plasmas Chemistry as a Tool for Environmental Pollutants Abatement Yan-hong Bai, Jie-rong Chen, Xiao-yong Li, and Chun-hong Zhang Environmental Fate and Global Distribution of Polychlorinated Biphenyls Angelika Beyer and Marek Biziuk Index.